The chemo-prophylactic efficacy of an ethanol Moringa oleifera leaf extract against hepatocellular carcinoma in rats - Kadry M. Sadek; Tarek K. Abouzed; Reham Abouelkhair; Sherif Nasr (Taylor & Francis Group, 2017)
Context: Hepatocellular carcinoma (HCC) is among the most well-known threatening tumours around the world, and the outlook remains bleak. Moringa oleifera Lam. (Moringaceae) exhibits antitumor, antioxidant and hepatoprotective properties. Objectives: To assess the chemo-prophylactic proficiency and other likely activities of Moringa oleifera leaf ethanol extract (MOLEE) against diethyl nitrosamine (DEN)-induced HCC. Materials and methods: Wistar rats were gastrogavaged with MOLEE (500 mg/kg) for one week and then gastrogavaged with MOLEE and DEN (10 mg/kg) for the following 16 weeks. The progressions of the histological components, serum biomarkers and oxidation of DNA of the liver tissues were resolved to assess the prophylactic impacts. The lipid oxidative biomarker, the cancer prevention agent status and apoptotic proteins were surveyed to assess the potential mechanisms. Results: The MOLEE LD50 was estimated to be 5585 mg/kg. MOLEE (500 mg/kg) administration fundamentally repressed the expansion event of knobs and the normal knob number per knob-bearing livers prompted by DEN, enhanced hepatocellular appearance and altogether significantly decreased (p < 0.05) DEN-induced elevations in serum biochemical records and hepatic 8-hydroxy-2-deoxyguanosine (8-OHdG) levels by 29%. The robotic studies found that MOLEE disrupted the DEN-activated oxidative reactivity damage in rats by 46.8%. Curiously, the expression of Bcl-2, Bcl-xl and β-arrestin-2 were fundamentally diminished (p < 0.05); however, the expression of Bax and caspase-3 were essentially (p < 0.05) upregulated. Discussion and conclusions: The outcomes presume that MOLEE inspired critical defensive impacts against DEN-induced hepatocarcinogenesis that might be identified with the implementation of antioxidant activity and actuation of apoptosis.